2012
DOI: 10.1890/11-0411.1
|View full text |Cite
|
Sign up to set email alerts
|

Carbon stocks across a chronosequence of thinned and unmanaged red pine (Pinus resinosa) stands

Abstract: Forests function as a major global C sink, and forest management strategies that maximize C stocks offer one possible means of mitigating the impacts of increasing anthropogenic CO2 emissions. We studied the effects of thinning, a common management technique in many forest types, on age-related trends in C stocks using a chronosequence of thinned and unmanaged red pine (Pinus resinosa) stands ranging from 9 to 306 years old. Live tree C stocks increased with age to a maximum near the middle of the chronosequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
31
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 61 publications
8
31
1
Order By: Relevance
“…The Nave et al, (2010) meta-analysis found that harvesting reduced soil carbon stocks in a small but significant way: forest floor carbon stocks decreased markedly and no influence was detected in the mineral soil, though great variation was identified between soil orders. This forest floor carbon stock reduction tendency for thinned stands is corroborated by several studies (e.g., Vesterdal et al, 1995;Jonard et al, 2006;Powers et al, 2012;Ruiz-Peinado et al, 2013), though other authors have reported little or no influence (Novák and Slodicák, 2004;Chatterjee et al, 2009;Jurgensen et al, 2012).…”
Section: Thinningsupporting
confidence: 82%
See 1 more Smart Citation
“…The Nave et al, (2010) meta-analysis found that harvesting reduced soil carbon stocks in a small but significant way: forest floor carbon stocks decreased markedly and no influence was detected in the mineral soil, though great variation was identified between soil orders. This forest floor carbon stock reduction tendency for thinned stands is corroborated by several studies (e.g., Vesterdal et al, 1995;Jonard et al, 2006;Powers et al, 2012;Ruiz-Peinado et al, 2013), though other authors have reported little or no influence (Novák and Slodicák, 2004;Chatterjee et al, 2009;Jurgensen et al, 2012).…”
Section: Thinningsupporting
confidence: 82%
“…In a chronosequence study on Pinus resinosa, Powers et al, (2012) found that thinning did not have a significant effect on total ecosystem carbon stock. However, in a previous study of the same species, Powers et al, (2011) found that thinning reduced the total carbon stock when these treatments were applied at 5-10 year interval.…”
Section: Thinningmentioning
confidence: 97%
“…Since forests act as the principal C storage system in terrestrial ecosystems and are sensitive to anthropogenic activity, appropriate forest management is considered important for C sequestration (Boerner et al 2008, Powers et al 2012. Thinning treatment, which is selective logging to enhance the value of forests, is known to alter the forest C storage by reducing the standing tree density and stimulating growth of the remaining trees (Zhou et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Dead organic matter, which originates from living organisms, accounts for approximately half of the forest C storage (Boerner et al 2008, Powers et al 2012. Fallen leaves, branches, and coarse woody debris (CWD) are the primary forms of dead organic matter, whose quantity and quality are related to the succession stage and forest management (Powers et al 2012, Ko et al 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation